One of the dimensions of human rights and sensitivity to its acceptance - Rebelo, Fernanda (2018)
This paper addresses the perceptions of the law students on human rights education, with regard to the purpose of the sentences, discussing whether they had learned the values passed on to them in class and if they were sensitive to this dimension of the human rights. As there is a popular tendency that, contradicting the Portuguese constitutional principles, defends more severe punishments, the article explored the reasons why the students’ perception and acceptance of these issues were aligned with this opinion. To achieve these objectives, data were collected through surveys with 13 questions answered by the Portucalense University students. The results showed that the students were not sensitised to the human rights dimension with regard to the purposes of sentencing. It was concluded that the majority of them were more receptive to the public opinion, published in the media channels, than to the knowledge that was provided to them in the Academy about the legitimation of the criminal punishment.